Technical Efficiency of Lampai Kuning Rice in Sijunjung, West Sumatra - Hasnah Hasnah; Riva Hendriani (Universitas Andalas, 2018)
This study aims to assess the performance of farming practices of Lampai Kuning rice as an improved variety. Data were collected using survey method that relied upon primary data generated during the 2016/2017 production season. Data were collected through the use of a set of structured questionnaire administered on thirty farmers in Nagari Aie Angek, Sijunjung Regency. Stata version 12 was used to test the stochastic frontier model to measure the efficiency of Lampai Kuning rice.The results showed that the use of manure and Urea had negative effect on the Lampai Kuning rice, while the use of NPK had positive effect. The level of technical efficiency of Lampai Kuning rice was very low at the 0,55 level. The study reveals that large land size led to high Lampai Kuning rice production. Farmers could double their rice production by using factor of production appropriately.